Assessment of body conformation traits and their relationship with production performance of Sahiwal cows - DEVI, INDU; KUMAR, AJAY; LATHWAL, S S; MISRA, A K; SINGH, PAWAN; MAMTA (The Indian Journal of Animal Sciences, 2023)
Linear type scoring is key component in decision making process in the herd, as it focusses on the selection of animals with higher productive potential based on their body conformation/linear traits. The present study was carried out on 150 lactating Sahiwal cattle of first to fifth parity. Measurements on linear type traits were recorded 1 h before the evening milking at three different stages of lactation. The average score point of objective linear type traits was stature 5.77±0.08, chest width 4.59±0.10, body depth 5.24±0.10, rump width 5.56±0.09, rump angle 4.48±0.08, rear legs sets 4.81±0.12, foot angle 4.84±0.10, fore udder attachment 4.85±0.11, rear udder height 5.52±0.10, udder depth 5.31±0.08, rear udder width 4.27±0.09, central ligament 4.01±0.09, fore teat length 3.49±0.10, rear teat length 3.94±0.09, teat circumference 4.20±0.11, teat diameter 4.16±0.10 and udder balance 5.25±0.11. On the other hand, average score point of subjective linear type traits (1-9 scale) was angularity 4.69±0.09, rear leg rear view 5.05±0.06, body condition score 6.53±0.08, locomotion 4.88±0.06, fore teat placement 4.41±0.07 and rear teat placement 6.28±0.08. Most of the body conformation traits in Sahiwal cattle were falling under intermediate category and of desirable type. However, some traits like stature, chest width, body depth, rump width, angularity, central ligament, rear udder height, rear udder width and fore udder attachment expressed scope for further improvement.